Data Literacy Training for K–12 Teachers: A Meta-Analysis of the Effects on Teacher Outcomes. (October 2022) - Filderman, Marissa J.; Toste, Jessica R.; Didion, Lisa; Peng, Peng
This meta-analysis explores training teachers in the use of data, defined as any quantifiable information that helps teachers know more about their students for instructional decision-making. The questions addressed are as follows: (a) What are the features of data literacy training for kindergarten through 12th-grade teachers? (b) What are the effects of data literacy training on kindergarten through 12th-grade teacher outcomes? (c) Do training characteristics moderate the effects of training? A comprehensive search of research conducted between 1975 and 2019 yielded 33 studies with 163 effect sizes that met inclusion criteria. Using a random effects model, the researchers found significant positive effects on knowledge and skills, g = .67, 95% confidence interval (CI) = [0.40, 0.93], and beliefs, g = .48, 95% CI = [0.17, 0.79]. A collaborative training format significantly and positively moderated effects. Implications for teacher trainings and the design of future research are discussed.